Diabetic Foot Care Service for Diabetic Patients – A National Survey Study of Community and General Hospitals in Thailand - Mirattanaphrai, Supalak; Cooney, Netima; Preechachaiyavit, Pornthip; Udomchairat, Rachanibool; Khonlaeaid, Sureeporn; Potisat, Somkiat (Journal of Health Science of Thailand, 2017)
Foot complications in diabetic patients are the major factors that influence the quality of life in patients. In order to improve the health care management system for patients with foot complications, base line information is required. This study aimed to survey the health service components regarding diabetic foot complications in all general and community hospitals in Thailand. Self-administered questionnaires were delivered to all general and community hospitals, a total of 802 hospitals, during April to September 2013. There were 480 hospitals returning the filled questionnaires. This was a 59.8 percent response rate. The results of the study showed that most of the hospitals evaluated foot complications and classified diabetic patients based on their risks. Although most hospitals had evaluated the appropriateness of patients’ footwear, only half of them were able to provide footwear and foot orthoses for patients with moderate or high risks. Regarding treatment, the majority of hospitals were able to treat patients with mild to moderate diabetic foot infection. This survey information is beneficial for policy planning regarding health care management system for patients with foot complications in Thailand.